PROMIS Computer Adaptive Tests Compared With Time to Brake in Patients With Complex Lower Extremity Trauma. Issue 11 (November 2016) - Kim, Chang-Yeon; Wiznia, Daniel H.; Averbukh, Leon; Torres, Andrea; Kong, Edward; Kim, Seewan; Leslie, Michael P.
Abstract : Objectives: To compare the PROMIS Physical Function and Pain Interference Computer Adaptive Tests (PROMIS PF CAT and PROMIS PI CAT) with time to brake (TTB) in patients with complex lower extremity traumas for evaluating whether patients can safely return to driving. Design: Prospective. Setting: Level-1 trauma center. Patients: Sixty-three patients with lower extremity injuries to the pelvis, acetabulum, hip, femur, knee, tibia/fibula, ankle, and foot within 15 weeks of treatment. Intervention: The TTB of patients with complex lower extremity trauma were tested at various time points postoperatively on a computerized driving simulator. Patients concurrently completed PROMIS PF CAT and PROMIS PI CAT. Main Outcome Measure: Correlations between TTB, PROMIS PF CAT, and PROMIS PI CAT. Results: The mean TTB for the healthy control group was 0.61 seconds. There was a statistically significant correlation between time since treatment and TTB (B = −0.008 s/d; P = 0.041) for right-sided lower extremity injuries below the knee (tibia/fibula, ankle, foot). TTB for right-sided injuries below the knee also significantly correlated with PROMIS PI CAT (B = 0.022; P = 0.029). The PROMIS PI CAT value was 43 when the healthy control group TTB was equal to 0.61 seconds. Conclusions: This study suggests that the PROMIS PI CAT can be used as an adjunct to the TTB in assessing whether a patient can safely return to driving.